Research priorities of adult intensive care nurses in 20 European countries: A Delphi study - Blackwood, B.; Albarran, J.; Latour, Jos (2011)
Aims: This paper is a report of a three round Delphi study of intensive care nursing research priorities in Europe (October 2006-April 2009). Background: Internationally, priorities for research in intensive care nursing have received some attention focusing on healthcare interventions and patient needs. Studies as early as the 1980s identified priorities in the United States, United Kingdom, Hong Kong and Australia. Research priorities of intensive care nurses across the European Union are unknown. Methods: The participants, invited in 2006, included 110 intensive care nurses, managers, educators and researchers from 20 European Critical Care Nursing Associations. Delphi round one was an emailed questionnaire inviting participants to list important areas for research. The list was content analysed and developed into an online questionnaire for rounds two and three. In round two, participants ranked the topics on a scale of 1-6 (not important to extremely important). Mean scores of round two were added to the questionnaire of round three and participants ranked the topics again. Results: There were 52 research topics in 12 domains. There was a dominance of priorities in five main areas: patient safety; impact of evidence based practice on outcomes; impact of workforce on outcomes; wellbeing of patients and relatives; and impact of end-of-life care on staff and practice. Conclusions: The results reflect worldwide healthcare concerns and objectives and highlight topics that nurses view as fundamental to the care of critically ill patients. These topics provide a platform for future research efforts to improve clinical practice and care of patients in intensive care.